STRATEGIC ANALYSIS OF DEVELOPMENT OF AGRICULTURAL ENTERPRISES OF IVANO-FRANKIVSK REGION - Yakubiv, V.M.; Boryshkevych, I.I.; Piatnychuk , I. D. (The actual problems of regional economy development, 2018)
Strategic analysis is an important method for the formation of substantiated, necessary and timely information necessary for building an effective development strategy of enterprises. The article analyzes the necessity of strategic analysis of agricultural enterprises as an important tool for determining the prospects of development in the modern market environment. The main aspects of strategic analysis of agricultural enterprises of Ivano-Frankivsk region have been investigated. Based on the analysis of strengths and weaknesses, existing opportunities and threats, the main strategic directions of development aimed at achieving the competitiveness of enterprises and further effective development have been identified.